Polar magneto-optical Kerr effect studies of interlayer exchange coupling in Fe/Tb bilayers and Fe/Au/Tb trilayers - Shypil, E.V.; Pogorilyy, A.M.; Pogoryelov, Ye.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Interlayer exchange coupling was studied. The investigations were carried out on bilayer (Fe/Tb) and trilayer (Fe/Au/Tb) ultrathin film structures. The films on silica substrate were prepared by electron-beam evaporation in an MBE system with a background pressure of (1 ·5) · 10⁻¹⁰ Torr and maintaining a pressure of (1 · 3) · 10⁻⁹ Torr during the film growth. To investigate these film structures polar magneto-optical Kerr effect was used. In bilayers the perpendicular magnetic anisotropy was observed. When a monolayer of Au was interposed at the interface, was observed to disappear. This is because of breaking the short-range interaction between Fe and Tb layers. Instead a long-range indirect exchange via nonmagnetic Au interlayer appears. The increase of Au interlayer thickness (3 · 35 Å) resulted in the oscillations of the Kerr angle. Analogous oscillations are distinctive to the RKKY model of interlayer exchange coupling.